Bulk phase behavior of lithium imide–metal nitride ammonia decomposition catalysts12. Issue 35 (23rd August 2018) - Makepeace, Joshua W.; Wood, Thomas J.; Marks, Phillip L.; Smith, Ronald I.; Murray, Claire A.; David, William I. F.
Abstract : Lithium imide is a promising new catalyst for the production of hydrogen from ammonia. This study reports the use of neutron and X-ray powder diffraction to investigate the presence of ternary nitrides in lithium-imide/metal nitride composite catalysts. Abstract : Lithium imide is a promising new catalyst for the production of hydrogen from ammonia. Its catalytic activity has been reported to be significantly enhanced through its use as a composite with various transition metal nitrides. In this work, two of these composite catalysts (with manganese nitride and iron nitride) were examined using in situ neutron and X-ray powder diffraction experiments in order to explore the bulk phases present during ammonia decomposition. Under such conditions, the iron composite was found to be a mixture of lithium imide and iron metal, while the manganese composite contained lithium imide and manganese nitride at low temperatures, and a mixture of lithium imide and two ternary lithium–manganese nitrides (Li x Mn2− x N and a small proportion of Li7 MnN4 ) at higher temperatures. The results indicate that the bulk formation of a ternary nitride is not necessary for ammonia decomposition in lithium imide–transition metal catalyst systems.